Analysis of Dried Onions in a Hybrid Solar Dryer, Freeze Dryer and Tunnel Dryer - Reyes-Salinas, A; Mahn-Osses, A (Italian Association of Chemical Engineering - AIDIC, 2015)
Onion (Allium cepa L.) belongs to the lily family, such as garlic and leeks. Dehydrated onion can be presented in powder, chunks, granules or slices. Its applications consider manufacturing of condiments, dehydrated or added to rehydrated meals. We determined the drying curves of onion slices cut into 10 and 5 mm thickness, using a hybrid solar dryer, a tunnel dryer and a freeze-dryer. Drying kinetics adjusted adequately with a phenomenological model and with four empirical models. The best fit was obtained with Ademiluyi empirical model. Diffusivity values obtained from the constant diffusivity model fluctuated between 10-08 and 10-10 m2 /s. Finally, rehydration curves were determined and their adjustment to the simplified constant diffusivity model resulted in diffusivity values between 10-6 and 10-7 m2/s. Copyright © 2015, AIDIC Servizi S.r.l.